Analisis Desain Penelitian Tindakan Kelas dan Kualitas Laporan Penelitian: Kajian Systematic Literature Review - Stella Dinda Dian Adisti; Nur Hidayah; Valentino Rahma Febrian; Intan Azzahro; Imron Fauzi (Advances In Education Journal, 2026)
Classroom Action Research (CAR) is a practice-based research approach that has the potential to improve the quality of learning through a continuous cycle of action and reflection. However, the quantitative growth in CAR publications has not been accompanied by a commensurate improvement in the methodological quality of resulting research reports. This study aims to analyze the design characteristics of CAR and identify factors influencing the quality of research reports. This study employs a Systematic Literature Review (SLR) method in accordance with the PRISMA 2020 guidelines. The literature search was conducted across four international academic databases Scopus, Web of Science, ERIC, and Google Scholar using a combination of keywords based on Boolean operators. The search yielded 127 articles, which were screened through three stages based on inclusion and exclusion criteria, resulting in 10 articles for further analysis. Data synthesis was conducted using a thematic narrative synthesis approach. The results indicate that most CAR research is oriented toward improving learning outcomes, however, recurring methodological weaknesses were identified, including: unclear problem formulations, weak coherence between action design and research objectives, limitations in data analysis techniques, and insufficient depth in the reflection process. This study contributes to the development of an evaluative framework for CAR designs that can serve as a reference for researchers in improving methodological standards and scientific credibility of CAR reports.